Performance analysis of resource allocation downlink for MIMO-OFDMA system using Greedy algorithm. / Azrinawati Samaon - Samaon, Azrinawati (2014)
Finding the optimization of power allocation of subcarrier is always a challenge in MIMO-OFDMA schemes in order to maximize the capacity of the system. Resources allocation is process how set of network is decide in wireless system. This research is to study restriction of proportional rate and total power among user in MIMO-OFDMA scheme and the power allocation and capacity of subcarrier in the scheme. The objectives are to suggest by using Greedy Power Allocation for capacity increment in MIMO-OFDMA system and to evaluate the system by Greedy Subcarrier Allocation. Simulation results show that the proposed algorithm can improve the capacity of the network compared with the waterfdling when using signal-to-noise ratio (SNR) with value 6dB. The proposed algorithm shows comparison between the noise to sub-channel ratio and power allocation in the midst of data sub-channel for 25, 75 and 100 users. It shows that there is no significant difference in power allocation of data subcarriers even if the number of users is increased.